Analisa pengaruh jumlah indentasi dan distribusi tegangan geser pada sambungan perekat baja-baja (paper ini telah dicabut) - Salman, S.; Sugiman, S.; Sulistyawati, E.D.; Zainuri, A.; Robiansyah, R. (Dinamika Teknik Mesin, 2019)
Adhesive joints are widely used in automotive industry and shipping industry. Efforts to increase the strength of the connection are still underway. This study aims to determine the effect of the amount of indentation on shear strength on low carbon steel joints and the failure mode when the number of indents is different. The connection was made of low carbon steel with epoxy adhesive as adhesive and adhesive thickness of 0.3 mm. The number of indents varied; with and without indentations 4, 9, 16, and 25 respectively. The indentation process was made by using pillar drilling with 1.5 mm diameter of drill bit. From the results, the specimen without indentation had highest shear strength was about 22 MPa. Connection strength tended to decrease with increasing indentation. By finite element modeling, the distribution of shear stress tended to be uniform without indentation, and the stress at the end of the connection for indented connections was higher than without indentation.